Advances in Exploration, Development and Utilization of Coal and Coal-Related Resources - Li, Jing; Cai, Yidong; Zhao, Lei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The development of clean and low-carbon energy is undoubtedly imperative in the coming decades worldwide. This book focuses on a series of advanced research on geological and geochemical characterization, as well as on the exploration, development, and utilization of coal and coal-related resources, especially critical metals together with unconventional gases in coal and coal-bearing sequences, which are of great significance to achieving carbon neutrality.